Effects of letrozole on catecholaminergic neurotransmitter levels, NCAM expression and cognitive functions in intact female rats - Yilmaz, Bayram; Aydin, Mehmet; Alcin, Ergul; Sahin, Zafer; Kutlu, Selim (Academic Press Inc Elsevier Science, 2006)
[Abstract Not Available]
6th International Congress of Neuroendocrinology -- JUN 19-22, 2006 -- Pittsburgh, PA